(untitled) (Journal of Ideas in Health, 2024)
Background: Medical students suffer from high levels of academic exhaustion, negative positions, and insufficient feelings about the academy. This study aims to estimate the rate of burnout among medical students and the related factors. Methods: A cross-sectional study was conducted from 1st March to 30th April 2023 at the medical college, Al-Nahrain University, Baghdad, Iraq. A self-administered standard Maslach Burnout Inventory-Student Survey Questionnaire was recruited to assess the burnout level depending on emotional exhaustion, cynicism, and professional efficacy questions. Descriptive and bivariate analyses were used to find out the association between variables. Results: Out of 515 medical students surveyed, 59.2% were females, and 31.7% lived in dormitories. Most were in their fourth year (32.6%), and 82.3% were non-smokers. About 12.6% had chronic illnesses, and 15.5% took regular medication. Stressful life events affected 65.2%, while 68.2% passed the last course. Over half (56.1%) slept less than eight hours daily, and only 21.7% exercised regularly. Among the sample involved in the study, 221 (42.9%) were suffering from a high burnout level. There was significant high burnout among females, who intake regular medication, were exposed to stress, failed in the last course, and those without regular exercise at P-values equal 0.01, 0.03, 0.002, < 0.001, and < 0.001 respectively. Conclusion: In conclusion, female gender, exposure to stress, the use of regular medications, academic failure, and aerobic lack are more likely related to high levels of burnout.